2002
DOI: 10.1103/physreva.65.063619
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman adiabatic passage from an atomic to a molecular Bose-Einstein condensate

Abstract: The process of stimulated Raman adiabatic passage ͑STIRAP͒ provides a possible route for the generation of a coherent molecular Bose-Einstein condensate ͑BEC͒ from an atomic BEC. We analyze this process in a three-dimensional mean-field theory, including atom-atom interactions and nonresonant intermediate levels. We find that the process is feasible, but at larger Rabi frequencies than anticipated from a crude single-mode lossless analysis, due to two-photon dephasing caused by the atomic interactions. We then… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(144 citation statements)
references
References 28 publications
3
140
1
Order By: Relevance
“…1. The exactly same description can be applied to the twophoton photoassociation-based Λ-system, due to the formal equivalence between the two models [15]. In Fig.…”
Section: Hamiltonian Stationary Equations and Cpt Statementioning
confidence: 99%
See 3 more Smart Citations
“…1. The exactly same description can be applied to the twophoton photoassociation-based Λ-system, due to the formal equivalence between the two models [15]. In Fig.…”
Section: Hamiltonian Stationary Equations and Cpt Statementioning
confidence: 99%
“…The situation when the collisions are present is more complicated. It was generally believed that the nonlinear phase shifts arising from particle collisions would defeat the two-photon resonance condition [13,15], a prerequisite for the existence of CPT states and hence the key for the successful implementation of STIRAP. In a recent work [23], we have shown that by appropriately chirping the optical frequency and the Feshbach detuning, the collision-induced nonlinear phase shifts can be dynamically compensated, hence generalizing the concept of the CPT state from the collisionless limit [13] to situations where collisions cannot be ignored.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that efficient short-pulse conversion requires asymmetric pulses [2,3]. The optimal density isρ ∼ 10 12 cm −3 , for which conversion to a molecular BEC occurs on a timescale T = 5 × 10 3 /χ 0 ∼ 50 ms. Optimizing the laser parameters [3] should give even further improvement.Granted, experiments are inhomogeneous and our theory is not. But inhomogeneity may be approximated by averaging over a Thomas-Fermi density distribution, and the subsequent optimal density should be in the same ballpark as the homogeneous prediction.…”
mentioning
confidence: 99%